Outcomes From Real-World Data on Intraoperative Electronic Radiotherapy for the Treatment of Early-Stage Breast Cancer: Long-Term Recurrence and Survival Outcomes From a Single Center - Dolores De la Mata; Bernardino Gabriel Santiago-Concha; Juan Enrique Bargalló-Rocha; Carlos Daniel Robles-Vidal; Daniella Gómez-Pue; Gerardo Castorena-Rojí; José Hinojosa-Gómez; Fabiola Flores-Vázquez; Mónika Blake-Cerda; Mario Enriquez-Barrera; Antonio Maffuz-Aziz (International Journal of Breast Cancer)
Conclusions: This is the first 10-year report about the effect of IORT on Mexican women with EBC in the early stages. Strict adherence to the selection criteria in this study resulted in low rates of side effects, mortality, and local recurrences, demonstrating that IORT is an effective treatment alternative for patients with EBC. Studies with a longer follow-up period should be performed, as recurrences can occur in the long term.